2014
DOI: 10.1021/jp5044464
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Purine Nucleotides by Triplet 3,3′,4,4′-Benzophenone Tetracarboxylic Acid in Aqueous Solution: pH-Dependence

Abstract: The photo-oxidation of purine nucleotides adenosine-5′-monophosphate (AMP) and guanosine-5′-monophosphate (GMP) by 3,3′,4,4′-benzophenone tetracarboxylic acid (TCBP) has been investigated in aqueous solutions using nanosecond laser flash photolysis (LFP) and time-resolved chemically induced dynamic nuclear polarization (CIDNP). The pH dependences of quenching rate constants and of geminate polarization are measured within a wide range of pH values. As a result, the chemical reactivity of reacting species in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Furthermore, we have demonstrated that based on the difference in g-factor, it is possible to differentiate between the two radicals utilizing only spectral and kinetic CIDNP data, despite of the close similarity in spin density distribution in the two investigated guanine radicals as discussed in Ref. [25] To identify the protonation position, heteronuclear CIDNP experiments are planned, namely, 15 N and 13 C CIDNP. The information presented can now be used to aid in the identification of transient guanine radicals involved in nucleic acid damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we have demonstrated that based on the difference in g-factor, it is possible to differentiate between the two radicals utilizing only spectral and kinetic CIDNP data, despite of the close similarity in spin density distribution in the two investigated guanine radicals as discussed in Ref. [25] To identify the protonation position, heteronuclear CIDNP experiments are planned, namely, 15 N and 13 C CIDNP. The information presented can now be used to aid in the identification of transient guanine radicals involved in nucleic acid damage.…”
Section: Discussionmentioning
confidence: 99%
“…[25] In the present study, measurements were performed at pH 6.2 and higher to exclude contributions of the reaction between GMP and triplet excited TCBP having two protonated carboxylic groups (pK a~4 .9). [25] In the present study, measurements were performed at pH 6.2 and higher to exclude contributions of the reaction between GMP and triplet excited TCBP having two protonated carboxylic groups (pK a~4 .9).…”
Section: Scheme Of the Photochemical Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using a photo‐sensitized chemical reaction one can also polarize purine nucleotides. In adenosine, the H2 and H8 protons can be efficiently polarized,, whereas in guanosine only the H8 proton exhibits CIDNP ,, . NMR detection for different nuclei, e. g., 13 C and 15 N, is also feasible: in studies of CIDNP of such hetero‐nuclei one can obtain detailed information on the spin density distribution in transient radicals ,.…”
Section: Cidnp Of Amino Acids and Nucleotidesmentioning
confidence: 97%
“…As photosensitizers, which are used to initiate a photo‐reaction giving rise to CIDNP, various dyes are used, which are listed in Scheme . These dyes are 2,2‐dipyridyl (DP),– 4‐carboxy‐benzophenone (4‐CBP),,, 3,3′,4,4′‐tetracarboxybenzophenone (TCBP),, and flavins with different substituents (flavin mononucleotide, FMN, is shown in Scheme ) ,,,. For running experiments under special conditions, i. e., at very low concentrations, one can also use other dyes, such as fluorescein .…”
Section: Cidnp Of Amino Acids and Nucleotidesmentioning
confidence: 99%